Some Geochemical Aspects of West Coast Coals û Implications for Quality Assessment and Utilisation (The Australasian Institute of Mining and Metallurgy, 1985)
For several years, the Geology Department of the University of Canterbury has hosted a series of postgraduate projects in the field of coal studies, supported principally by the Ministry of Energy and to a lesser extent by private companies. These projects have involved mainly West Coast Coalfields, and my own studies have focussed on inorganic geochemical aspects of West Coast coals. Because of the large number of potentially important analyte elements in coal, and the wide diversity of coals occurring in the West Coast region, this project has required a substantial amount of work to be spent on sample collection, sample preparation, development of analytical methods, and actual analysis. Considerable problems must be faced at the sampling stage: Can sufficient information be obtained from whole-seam composites, or should seams be sampled in plies. Ply analysis is preferable, but results of proximate analyses are usually available for composites only. Where multi-seam drillhole samples become available (eg Greymouth Coalfield, where some holes yielded more than six sampled seams), the ply option involves a dramatic increase in the number of samples. I have attempted to strike a workable compromise between geographical coverage of coalfields, and detailed sampling of individual seams at each locality. In many cases, sample material has been used jointly with Jane Newman who has carried out petrographic studies.